TANAMAN KANGKUNG HIDROPONIK DAN KAMPUNG WARNA - Sugeng Hadi Purnomo (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2017)
Hydroponics is also known as the cultivation of plants without media. Hydroponiccultivation does not require a large area. Provided that the fulfillment of nutritionalneeds for the relevant plants are met and enough sunlight, then one can already growcrops using hydroponics as a medium. Since the area of RW06 and RW12 Putat JayaSub-District of Sawahan District formerly Dolly's ex-localization area (